IMPLEMENTASI MODEL CRISP-DM UNTUK MENENTUKAN SALES PIPELINE PADA PT X - Dina Feblian; Dadan Umar Daihani (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
PT X is a joint venture subsidiary of a bank in Indonesia, which is a company, engaged ingeneral insurance business. PT X is required to increase its share of the parent company by theshareholders in developing its business potential. In developing the potential of the business, companiesneed enough information to be analyzed further. Sources of information that can be used is the businessdata of the company, both of PT X as a subsidiary and its holding company. By utilizing business datain large numbers, the company will find a variety of information needed. For the business dataprocessing required a technique of data mining. In a study conducted, the implementation of the modelrefers to the six stages of Cross-Industry Standard Process for Data Mining or commonly known by theacronym CRISP-DM. In doing data mining, the six phases of the CRISP-DM is business understanding,understanding the data, the data preparation, modeling, evaluation, and deployment. At this stage ofdeployment, the report will be made by the customer segmentation by region. The expected result is theinformation required in the form of a new customer pipeline.